Inclusion of Ethical Aspects in Multi-criteria Decision Analysis - Sapienza, Gaetana; Dodig-Crnkovic, Gordana; Crnkovic, Ivica (2016 1st International Workshop on Decision Making in Software ARCHitecture (MARCH), 2016)
Decision process is often based on multi-faceted and mutually opposing criteria. In order to provide rigorous techniques for problem structuring and criteria aggregation used for classification and ranking of alternatives, Multiple Criteria Decision Analysis (MCDA) has been used as a method to achieve architectural decisions. Even though it has already been argued in literature that MCDA essentially depends on value systems of decision-makers, it is a question how the decision result reflects a particular criterion, requirement or a particular decision. This is especially true if a criterion is not precisely specified. In this paper we analyse the ethical aspects of MCDA. In our analysis we argue that it is in the long run necessary to make value basis of decision-making and ethical considerations explicit and subject for scrutiny. As a support to encourage introduction of transparent value-based deliberation we propose an extended MCDA scheme that would explicitly take into account ethical analysis. As an illustration, we present an industrial case study for the Software (SW)/Hardware (HW) partitioning of a wind turbine application in which different decisions can be taken, depending on the ethical aspects.